Effect of cobalt electroless deposition on nickel hydroxide electrodes - Ortiz, Mariela Gisela (2014)
The effects of cobalt additive on the positive electrode surface of nickel alkaline batteries are investigated. Electrode surface modifications by electroless cobalt deposits were made at different immersion times. The performance of nickel hydroxide electrodes was studied by optical techniques, such as scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX) and electrochemical methods as cyclic voltammetry, charge–discharge curves and electrochemical impedance spectroscopy (EIS). According to these results, electroless cobalt deposits obtained with 5 min of immersion time in the electroless-bath exhibit a better electrode performance.